Increasing Number of Older Persons National, Regional and Global Prospects - Omotayo, Olatubosun Tope; Sofadekan, Adedayo Oyewole (NIU Journal of Humanities, 2021)
The study gives a concise submission on global effort in addressing the increasing number of older persons; such as Vienna 1982 and Madrid International Plan of Action on Ageing in 2002 by the United Nations. The paper presents the concept of global ageing that proved the increasing and continual involvement of older persons in societal issues and institutions such as family, job, retirement, crime, sports and romance. Besides, ageism that concerns prejudice against older persons that cut across academia, commerce, education, international organizations and social institutions, proved that the increasing number of older persons is not getting the needed attention. Therefore, the paper advocates for national, regional and global effort on ageing. The position of the paper is that nations should set up commission for ageing while regional bodies like the African Union should have a commission for ageing ditto for United Nations that will globally blanket the issues of ageing. These become necessary as the United Nations even the African Union do not have a designated commission on ageing; while the number of older persons continues to increase. Finally, it gives recommendations on how best to mainstream the global efforts. Keywords: Ageing, Wellbeing, Sustainable Development, Genrontological, Retirement